Gambaran Emotional Exhaustion Pada Penyidik Wanita Unit Pelayanan Perempuan dan Anak (PPA) Satuan Reskrim Polresta Banjarmasin - Warapsari, Reska Maulidya; Marsha, Gladis Corinna; Fitriah, Aziza (Innovative: Journal Of Social Science Research, 2025)
This study aims to explore the emotional exhaustion experienced by female investigators in the Women and Children Services Unit (PPA) of the Criminal Investigation Department at Polresta Banjarmasin in handling cases involving Children in Conflict with the Law (ABH). Emotional exhaustion is a condition of emotional fatigue caused by job pressure, high workload, lack of social support, and role-related stress. This study uses a qualitative approach with a case study method. Data collection techniques included semi-structured interviews, passive participant observation, and documentation. The findings reveal that workload and time pressure significantly contribute to emotional exhaustion, while lack of social support and role stress appeared but were less dominant. The study highlights the importance of psychological support and counseling systems for investigators and the need for greater institutional attention to the mental well-being of female investigators, especially those handling sensitive cases like ABH.